Review of Post-traumatic Osteoarthrosis and Medical-legal Approaches to Address It (2018)
Purpose: Joint trauma can lead to a range of acute injuries. Although acute symptoms disappear, and some lesions can be surgically repaired, the joint lesion can trigger a chronic process of remodeling in the cartilage and other joint tissues that may manifest as posttraumatic osteoarthrosis (ptoa). The purpose of this paper is to compile updated information on the criteria for forensic assessment of individuals who may develop this condition, in the context of the Colombian criminal system. Period covered, origin and types of publications: Articles from Pubmed databases published in the last 15 years were reviewed with the listed descriptors and a secondary search for references was made to answer the questions asked. Point of view: Posttraumatic osteoarthrosis has variable frequencies according to the type of joint injury, and its follow-up is clinical and radiological. Currently, there are tendencies to make diagnoses prior to its diagnosis, including the presence of biomarkers. Conclusions: The review showed that to diagnose ptoa in serious injuries can take between two and five years, and even “decades for less severe fractures.” The prolonged time to diagnose ptoa causes problems for the forensic approach. Risk factors for developing ptoa in some types of joint injury are identified, while forensic recommendations are made to draw related conclusions.